Effect of Aggregates Packing with the Maximum Density Methodology in Pervious Concrete - Arcolezi, Karina H. [UNESP]; Silva, Rodrigo G. da [UNESP]; Soriano, Lourdes; Borrachero, Maria V.; Monzo, Jose; Paya, Jordi; Tashima, Mauro M. [UNESP]; Akasaki, Jorge Luis [UNESP] (Mdpi, 2023)
The granulometric distribution of the aggregates used in pervious concrete can significantly impact its mechanical and hydraulic properties by modifying granular skeleton and pore distribution. The unit weight increases when single-sized aggregates are combined, which results in improved mechanical properties. In this study, the maximum density methodology was applied to enhance pervious concrete's mechanical strength by using three narrow-sized basaltic aggregates and their combination. The experimental results showed that the mechanical performance of the samples created with packed aggregates improved compressive strength by up to 81.2% and the energy support impact was higher than 225 J (50% higher than the reference sample) after curing for 28 days. Although the densification of packing aggregates increased, the greatest reduction in porosity was 24.3%. The lowest infiltration rate was 0.43 cm/s, a satisfactory value according to the literature. These findings suggest that the aggregates packing methodology is effective in producing optimized and sustainable pervious concretes.
Keywords: compressive strength; impact resistance; infiltration rate; physical properties; pore characterization